2019
DOI: 10.3386/w26240
|View full text |Cite
|
Sign up to set email alerts
|

Conference Presentations and Academic Publishing

Abstract: We quantify the contribution of conferences to publication success of more than 4,000 papers presented at three leading economics conferences over the 2006-2012 period. We show a positive link between conference presentation and the publishing probability in high-quality journals. Participating in major conferences is also associated with improved metrics for other measures of academic success such as the number of citations or abstract views. While the results are broadly similar across fields, annual meeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Looking at the Federal Reserve System (Fed), Gorodnichenko et al. (2021) document that its social media content focuses on monetary policy, financial markets, and economic issues in around 50% of the cases, while the remaining posts are used to disseminate research output, advertise media interviews or job vacancies 17 . Importantly, they also show that the majority of Twitter users that engage with the Fed by retweeting or mentioned it are indeed users which cannot be classified as media, academics, investors, government organizations, or politicians, that is, the general public.…”
Section: Central Bank Facebook Linkedin Twittermentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at the Federal Reserve System (Fed), Gorodnichenko et al. (2021) document that its social media content focuses on monetary policy, financial markets, and economic issues in around 50% of the cases, while the remaining posts are used to disseminate research output, advertise media interviews or job vacancies 17 . Importantly, they also show that the majority of Twitter users that engage with the Fed by retweeting or mentioned it are indeed users which cannot be classified as media, academics, investors, government organizations, or politicians, that is, the general public.…”
Section: Central Bank Facebook Linkedin Twittermentioning
confidence: 99%
“…This methodology has also been used in Gorodnichenko et al. (2021) (see Section 4.1 for a summary of their findings).…”
mentioning
confidence: 99%
“…Similarly, one could argue that the role played by nationality, editorship, and the University one works is due to the network effects they create because network studies have shown that people connect with people similar to themselves, the so-called homophily property (e.g., Freeman & Huang, 2015). Further, Gorodnichenko et al (2019) show that presenting at the AEA, EEA, or RES conferences increases the probability of the paper being published in a high-quality journal.…”
Section: Factors Affecting Performancementioning
confidence: 99%